Determinants of quality in airline service: the user’s view of a developing country - Guimaraes Junior, Djalma Silva; Melo, Fagner José Coutinho de; Sant’anna, Carlos Henrique Michels de; Xavier, Larissa de Arruda; Medeiros , Denise Dumke de (Brazilian Journal of Operations & Production Management, 2024)
Goal: This paper aims to identify the dimensions that impact the perception of the quality of Brazilian air services in the eyes of customers, using a questionnaire based on the SERVPERF model adapted for the service studied as a data collection instrument. Design/Methodology/Approach: The research used a quantitative approach, in which 810 questionnaires were analyzed using Structural Equation Modeling methodology. Results: The results showed that the relationship between quality perceived by clients and the dimensions of quality Tangibles and Empathy were those confirmed by Structural Equation Modeling in this research. The fact that the study is exploratory, and temporal indicates that in this period, Brazilian consumers attach more importance to the environment and appearance of aircraft, equipment, and employees of the companies and that their needs are met in a personalized way. Limitations of the investigation: Only Tangibles and Empathy dimensions were confirmed. Practical implications: With the feedback of the customer, including the constant need for an accuracy of the assumptions and hypotheses studied in this paper, an airline can identify what the real needs of its customer must be met and, in its strategic planning, identify the possible actions to be implemented, such as the priority of the investments, and, thus, to be able to increase the competitive advantage, offering the clients what they prioritize. Originality/Value: The information brought by this research can support the development of business strategies oriented in aspects related to tangible elements and empathy in the service to add value to the service perceived by the clients, contributing to the development of the activity and the sector.